Lightning radiation field spectra of cloud flashes - Sonnadara, D.U.J.; Cooray, Vernon; Fernando, Mahendra (My University, 2004)
Electric radiation fields produced by lightning cloud flashes have been Fourier analysed to obtain amplitude spectra for frequencies in the range of 20 kHz to 20 MHz. The spectra were generated by analysing the first 10ms time window of cloud flashes and they show f-1 frequency dependence up to 2 MHz followed by f-2 dependence and higher for frequencies above 2 MHz. By utilizing digital filters it has been shown that measurements taken with narrow band filters do agree with the results produced under wide band measurements.
Keywords: Lightning; Radiation field spectra; Cloud flashes